Awareness and prevalence of cervical cancer risk factors among adult women in Kuala Selangor / Nurul Hazwani Hamid - Hamid, Nurul Hazwani (2016)
Cervical cancer has become one of serious burden on reproductive health of women worldwide although it is preventable. In Malaysia, cervical cancer had been ranked as the second most frequent cancer among women after breast cancer especially between 15 and 44 years of age. Numerous risk factors are associated with cancer and 80 % of deaths from cancer are due to unhealthy lifestyle practices such as nutritional deficiencies, sedentary lifestyles, and smoking. Therefore, awareness and knowledge play important role for cancer prevention. The main objective of this study is to assess the awareness levels besides the prevalence of cervical cancer risk factors among adult women in Kuala Selangor, Malaysia. Convenience-sampling method was chosen in this study to obtain the data from self-administered questionnaire that had been carried out on 73 adult women that fulfil the inclusion criteria. The participants were provided with a self-administered questionnaire to be completed that had been adapted from Cancer Awareness Measure (CAM) questionnaire specialised on cervical cancer and several studies. The questionnaire consists of three main parts that covered socio-demographic data, awareness on cervical cancer risk factors as well as the signs and symptoms and also the screening test. Out of 73 adult women, the mean age was 22.6 (±9.99), 43.8 % of respondents had moderate level of awareness on cervical cancer risk factors, approximately about 52.1 % had low awareness on the cervical cancer signs and symptoms, 41.1 % were aware on cervical cancer screening and vaccination, and 72.6 % of respondents had prevalence of 20 % to 49 % of cervical cancer risk factors. In conclusion more efforts must be focused to provide proper education and reassurance our young females about danger health issues. This study provides crucial information that might that can improve the level of awareness and knowledge among Malaysian females.